Peningkatan Pembungaan dan Hasil Biji Bawang Merah Varietas Bima melalui Vernalisasi dan Aplikasi GA3 - Dian Fahrianty; Roedhy Poerwanto; Winarso Drajad Widodo; Endah Retno Palupi (Institut Pertanian Bogor, 2020)
The low production of true seed of shallot (TSS) is mostly caused by a low flowering rate. The research was aimed to increase the flowering rate and seed yield in lowland (240 masl) and highlands (1250 masl) by vernalization and submersion of the seed bulbs in GA3 before planting. The research was arranged in a completely randomized block design with 2 factors and replicated four times. The first factor was vernalization, i.e. without and with vernalization at 10±2°C for 30 days, and the second factor was the submersion of the seed bulbs following vernalization in GA3 at the concentrations of 0, 100, and 200 ppm for 1 h. Parameters measured were time of 50% flowering (days after planting), percentage of flowering plants, number of umbel per plant, number of floret per umbel, fruitset, seed weight per umbel and per plant, as well as the percentage of seed germination. The result suggested that when production of TSS of var. Bima is to be carried out in the lowland then the seed bulbs had to be vernalized at 10±2°C for 30 days which will increase the flowering percentage and seed yield. If the production of TSS is to be carried out in the highland then vernalization at 10±2°C for 30 days will increase the flowering percentage and seed yield. However, if for any reason vernalization is impossible to proceed then the submersion of the seed bulbs in 100 ppm GA3 for 1 h was sufficient to increase the flowering percentage and seed yield. The produced seeds (TSS) either in the low as well as in the highlands had high germination percentages. Keywords: germination, highland, lowland, umbel, true seed of shallot